1992
DOI: 10.1111/j.1365-2222.1992.tb02070.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory allergies (bronchial asthma and rhinitis) due to sensitization of type I allergy to red spider mite (Panonychus ulmi KOCH)

Abstract: The inhabitants of a fruit growing area often report spontaneously of sensitization to the red spider mite (RSM) (Panonychus ulmi KOCH). These are for the most part sensitizations with low clinical symptoms (rhinitis, conjunctivitis and erythema). Severe clinical developments with bronchial asthma have been observed. We investigated six patients working in a fruit growing area sensitized by RSM. The sensitizations corresponded to a Type I allergy. Skin tests and provocation tests (nasal as well as bronchial) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…In populations at risk, such as agriculture workers dealing with fruit trees or greenhouse vegetables, the sensitization rates are high, in the range of 36% [13] to 100% [32]. Epidemiologic studies have also demonstrated high rates of sensitization in the surrounding population, which is not occupationally exposed to apple trees [21] or citrus trees [24][25][26]. Significant differences in the rate of sensitization to these mites have also been identified between children residing in rural or urban areas [33].…”
Section: Mites Of Allergenic Importance In Agricultural and Occupatiomentioning
confidence: 91%
See 1 more Smart Citation
“…In populations at risk, such as agriculture workers dealing with fruit trees or greenhouse vegetables, the sensitization rates are high, in the range of 36% [13] to 100% [32]. Epidemiologic studies have also demonstrated high rates of sensitization in the surrounding population, which is not occupationally exposed to apple trees [21] or citrus trees [24][25][26]. Significant differences in the rate of sensitization to these mites have also been identified between children residing in rural or urban areas [33].…”
Section: Mites Of Allergenic Importance In Agricultural and Occupatiomentioning
confidence: 91%
“…Among the mites present in horticultural environments, the following have clinical importance: phytophagus mites belonging to the family Tetranychidae [10][11][12][13][14][15][16][17][18][19][20] (genera Tetranychus and Panonychus) [21][22][23][24][25][26], and predator mites belonging to the families Phytoseiidae (genera Phytoseiulus and Amblyseius), Dermanyssidae (genus Hypoaspis) [27,28,29•], and Hemisarcoptidae (genus Hemisarcoptes) [30]. The main symptoms associated with sensitization and exposure to Tetranychidae mites (red spiders) are rhinoconjunctivitis and asthma.…”
Section: Mites Of Allergenic Importance In Agricultural and Occupatiomentioning
confidence: 99%
“…To date, two papers have been published dealing with allergy lo a dilVcrcnt red spider mile: Panonychus ulmi, which belongs to the Tetranychydae ^amWy [13,14], In the latter reference, Kroidl etal. [14] have shown a case report of type I hypersensitivity to P. ulmi.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] They are classified in the order Prostigmata, family Tetranichidae, subfamily Tetranichynae. The other spider mite, citrus red mite (Panonychus citri), is the most important inhalant allergen related to occupational asthma found in citrus farm farmers.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 All previous TSM-related reports have been confined to occupational exposures. [2][3][4][5][6][7][8] Although house-dust mite (HDM) has been known as the most important allergen in Korea, 11 a recent investigation demonstrated that TSM could be one of the prevalent inhalant allergens in nonfarmers as well as farmers in pear orchards. 12 Skin prick test (SPT) results of adult asthmatic patients complaining of summer-type asthma indicated that TSM was second in prevalence of sensitivity to HDM.…”
Section: Introductionmentioning
confidence: 99%